Evaluation of the SNOWPACK model's metamorphism and microstructure in Canada: a case study. (3rd September 2018) - Madore, Jean-Benoit; Langlois, Alexandre; Côté, Kevin
ABSTRACT: The snow thermodynamic multi-layer model SNOWPACK was developed to address the risk of avalanches by simulating the vertical properties of snow. Risk and stability assessments are based on the simulation of the vertical variability of snow microstructure, as well as on snow cohesion parameters. Previous research has shown systematic error in grain size simulations (equivalent optical grain size) over several areas in northern Canada. To quantify the simulated errors in snow grain size and uncertainties in stability, the snow specific surface area (SSA) was measured with a laser-based instrument. Optical grain size was retrieved to validate the optical equivalent grain radius from SNOWPACK. The two study plots are located in Glacier National Park, BC, and Jasper National Park, AB, Canada. Profiles for density and stratigraphic analysis were obtained as well as grain size profiles, combined with snow micropenetrometer (SMP) measurements. Density analysis showed good agreement with the simulated values ( R 2 = 0.76). Optical grain size analysis showed systematic overestimation of the modeled values, in agreement with the current literature. The error in SSA evolution for a rounding environment was mostly constant, whereas error for conditions driven by a temperature gradient was linked to the size of the facetted grains.